Suicide in nursing professional voice and intervention strategies before the suicidal behavior - Nara Reisdorfer; Graciela Machado de Araujo; Leila Mariza Hildebrandt; Taciana Raquel Gewehr; Janaine Nardino; Marinês Tambara Leite (Universidade Federal de Santa Maria, 2015)
Aim: to analyze nursing professionals' understanding and intervention strategies, in a general hospital, on suicidal behavior. Method: qualitative and descriptive study, performed with 10 professionals from a general hospital. Semi-structured interviews were used for data collection and the data analysis followed the steps of thematic analysis. Results: the results were grouped in two themes, the first refers to the professionals' conception about suicide while the second discusses the interventions concerning the people who attempted or at risk for suicide. Final remarks: the nursing staff has weakness in knowledge of suicidal behavior which results in the interventions. This fact highlights the importance of the need for qualification of these professionals in order to provide effective care to people at risk or that has attempted suicide